2011
DOI: 10.1242/dev.066126
|View full text |Cite
|
Sign up to set email alerts
|

Otic ablation of smoothened reveals direct and indirect requirements for Hedgehog signaling in inner ear development

Abstract: SUMMARYIn mouse embryos lacking sonic hedgehog (Shh), dorsoventral polarity within the otic vesicle is disrupted. Consequently, ventral otic derivatives, including the cochlear duct and saccule, fail to form, and dorsal otic derivatives, including the semicircular canals, endolymphatic duct and utricle, are malformed or absent. Since inner ear patterning and morphogenesis are heavily dependent on extracellular signals derived from tissues that are also compromised by the loss of Shh, the extent to which Shh si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 65 publications
6
86
1
1
Order By: Relevance
“…Shh produced by the notochord and floor plate acts as a morphogen to pattern the DV neural tube (Dessaud et al, 2008), and this diffusible signal also acts directly on the developing amniote otocyst to confer DV patterning (Riccomagno et al, 2002;Bok et al, 2007b;Whitfield and Hammond, 2007). Shh effectors, such as the Gli transcription factor family, and direct targets of Shh signaling, such as the Shh receptor patched 1 (Ptc1, or Ptch1), are expressed in the otocyst epithelium in a dorsal-to-ventral gradient, indicative of a graded response to Shh (Bok et al, 2007c;Brown and Epstein, 2011). Perturbation of Shh signaling with antibodies or in Shh mutant mice leads to a loss or reduction of transcription factors expressed in the ventral regions of the otocyst with a Box 1.…”
Section: Patterning Of the Inner Ear Primordiummentioning
confidence: 99%
See 1 more Smart Citation
“…Shh produced by the notochord and floor plate acts as a morphogen to pattern the DV neural tube (Dessaud et al, 2008), and this diffusible signal also acts directly on the developing amniote otocyst to confer DV patterning (Riccomagno et al, 2002;Bok et al, 2007b;Whitfield and Hammond, 2007). Shh effectors, such as the Gli transcription factor family, and direct targets of Shh signaling, such as the Shh receptor patched 1 (Ptc1, or Ptch1), are expressed in the otocyst epithelium in a dorsal-to-ventral gradient, indicative of a graded response to Shh (Bok et al, 2007c;Brown and Epstein, 2011). Perturbation of Shh signaling with antibodies or in Shh mutant mice leads to a loss or reduction of transcription factors expressed in the ventral regions of the otocyst with a Box 1.…”
Section: Patterning Of the Inner Ear Primordiummentioning
confidence: 99%
“…Since Hh signaling is known to influence DV patterning of both neural and mesenchymal tissue (Chiang et al, 1996;Fan et al, 1995), it is formally possible that Shh is regulating inner ear DV patterning through both direct effects on the otic epithelium and indirect effects on the patterning of tissues adjacent to the otocyst. A recent study in which the Shh receptor smoothened (Smo) was conditionally inactivated in the otocyst suggests that both mechanisms pattern the otocyst (Brown and Epstein, 2011). In Smo conditional mouse mutants, the ventral inner ear (cochlea and saccule) is absent, but dorsal components of the inner ear (semicircular canal, endolymphatic duct, cristae and utricle; see Glossary, Box 1) develop normally.…”
Section: Patterning Of the Inner Ear Primordiummentioning
confidence: 99%
“…The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011). The Pax2-Cre transgenic allele was created using a BAC that contains a 101-kb region 5′ to the mouse Pax2 gene as well as 20 kb of the Pax2 coding region, which includes the first three exons of the Pax2 gene.…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%
“…SHH signaling, in contrast to WNT signaling, patterns the ventral otocyst and is required for formation of the cochlear duct. Absence of SHH signaling in Shh −/− mouse embryos, or ablation of the embryonic tissue secreting SHH (notochord and floor plate of the neural tube) in chick embryos, results in complete loss of the cochlear duct (Bok et al, 2005(Bok et al, , 2007bBrown and Epstein, 2011;Riccomagno et al, 2002).…”
Section: Introductionmentioning
confidence: 99%